Early Diagnosis of Sepsis in Emergency Departments, Time to Treatment and Association with Mortality - Khaliq Ur Rehman, Rizwan Aziz Qazi, Tahir Mukhtar Sayed, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Sepsis is a major cause of mortality associated with emergency department (ED) visits. In 2018, the Surviving Sepsis Campaign (SSC) recommended the following strategy to improve patient survival rates. Objectives: The main objective of the study is to find the early diagnosis of sepsis in emergency departments, time to treatment and association with mortality. Material and methods: This cross sectional study was conducted in Akbar Niazi Teaching Hospital, Barakahu, Islamabad during March 2022 till August 2022. The data was collected with the permission of ethical committee of hospital. The inclusion criteria were clinically suspected infection on presentation to an emergency department and at least two systemic inflammatory response syndrome signs, not including high leukocyte counts. Results: Out of 100 patients with sepsis, 97 were included for analysis, exclusions being due to incomplete information. 54% were male and 46% female. The age distribution was similar in both the genders with mean age being 54±2 years in males and 50±2 in females (p=0.30). Diabetes mellitus was the leading co-morbid present in 21 males as opposed to 18 females, followed by hypertension in 22 males and females respectively. Practical implication: This study will help in finding the procedure of sepsis and organ failure. Conclusion: It is concluded that procedures for recognizing sepsis and organ failure in the emergency department were delayed or not carried out in a substantial proportion of patients with sepsis. Keywords: Sepsis, Patients, Failure, Survival, Fluid